Linguistics as Geopolitical Strategy: Framing, Legitimacy, and Power in Global Discourse - Iskandarsyah Siregar (PT FORMOSA CENDEKIA GLOBAL, 2026)
This study investigates the strategic function of linguistics in forming transnational geopolitical configurations from 2015 to 2025. The paper draws from 250 purposively sampled texts official speeches, media releases, and mainstream news and media coverage, from the US, Russia, China, and the European Union. Critical Discourse Analysis (CDA), semiotics, and linguistic pragmatics serve as the conceptual basis to explain how political elites employ discourse strategies to shape a global public opinion by using strategies such as framing, euphemism, delegitimising opponents' claims, and conceptual metaphors. Quantitatively, the study indicates framing (35%) and euphemism (28%) when utilised by the United States and China, respectively, served to strengthen legitimacy for foreign policy, to frame 'good' narratives, delegitimisation (22%) was used mainly by the EU and Russia to frame a good enemy, and conceptual metaphors (15%) - though the least used, were also effective in framing normative imperatives.